(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Tuberculosis is one of the diseases of greatest social importance to humanity. Pulmonary tuberculosis is the most widespread and contagious form of tuberculosis, which is not only a medical but also a social problem. According to the World Health Organization (WHO), millions of new cases are recorded worldwide every year. In Uzbekistan, the fight against tuberculosis is also carried out at the state level. However, currently, under the influence of various factors, new trends are observed in the epidemiology of the disease.